Spin Quintet in a Silicon Double Quantum Dot: Spin Blockade and Relaxation - Theodor Lundberg (American Physical Society, 2020)
Spins in gate-defined silicon quantum dots are promising candidates for implementing large-scale quantum computing. To read the spin state of these qubits, the mechanism that has provided the highest fidelity is spin-to-charge conversion via singlet-triplet spin blockade, which can be detected in situ using gate-based dispersive sensing. In systems with a complex energy spectrum, like silicon quantum dots, accurately identifying when singlet-triplet blockade occurs is hence of major importance for scalable qubit readout. In this work, we present a description of spin-blockade physics in a tunnel-coupled silicon double quantum dot defined in the corners of a split-gate transistor. Using gate-based magnetospectroscopy, we report successive steps of spin blockade and spin-blockade lifting involving spin states with total spin angular momentum up to S=3. More particularly, we report the formation of a hybridized spin-quintet state and show triplet-quintet and quintet-septet spin blockade, enabling studies of the quintet relaxation dynamics from which we find T_{1}∼4  μs. Finally, we develop a quantum capacitance model that can be applied generally to reconstruct the energy spectrum of a double quantum dot, including the spin-dependent tunnel couplings and the energy splitting between different spin manifolds. Our results allow for the possibility of using Si complementary metal-oxide-semiconductor quantum dots as a tunable platform for studying high-spin systems.